A preparation method of a strain-regulated room-temperature ultra-wide spectrum polarization detector
By preparing alumina and hexagonal boron nitride films on flexible polyimide films, and combining them with ZrTe5 films and metal interdigitated electrodes, the problem of strain control of polarization detectors on rigid substrates was solved, achieving broadband polarization detection with low pollution and low dark current.
Patent Information
- Application Number
- CN202310941379.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-07-28
AI Technical Summary
Existing polarization detectors are difficult to strain control when fabricated on rigid substrates, resulting in severe surface contamination and excessively high dark current, which limits their application in ultraviolet-terahertz ultrawideband polarization detection.
Using polyimide film as substrate, aluminum oxide film is deposited by atomic layer deposition technology, combined with the transfer technology of hexagonal boron nitride and PDMS film, ZrTe5 film is prepared, and metal interdigitated electrodes are formed by thermal evaporation process to realize strain-controlled photoelectric converter.
It reduced the surface contamination rate of photoelectric conversion materials, controlled dark current, expanded the operating band, improved carrier transport velocity and temperature tolerance, and realized broadband polarization information detection.
Smart Images

Figure CN116914022B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of photoelectric detection technology, and in particular to a method for fabricating a strain-controlled room temperature ultrawideband polarization detector. Background Technology
[0002] Polarization is one of the most important pieces of information about light. Polarization detection can extend light intensity information from three dimensions (amplitude, spectrum, space) to seven dimensions (amplitude, spectrum, space, degree of polarization, orientation angle, ellipticity, and rotation direction), significantly improving the accuracy of target detection and object recognition. Traditional polarization detection systems are complex, requiring a pre-polarizing array, external filters, amplification circuits, and complex decoding algorithms to output digital information. This makes polarization systems bulky, limiting their miniaturization applications. Traditional semiconductor photoelectric converters are limited by their selective transitions, resulting in a very limited operating wavelength range for polarization detectors. Achieving ultraviolet-terahertz room-temperature polarization detection in a single device is the core technology of polarization detection systems, and it has enormous development potential driven by the broad market prospects of broadband polarization detection technology.
[0003] Currently, ultraviolet-terahertz ultrawideband polarization detection mainly utilizes ferroelectric modulation, thermal effects, field enhancement effects, photo-induced gate voltage effects, and narrow bandgap semiconductors. Except for narrow bandgap semiconductors, all of these methods are limited by external environmental factors such as temperature and applied electric fields. Although narrow bandgap semiconductors can achieve ultraviolet-terahertz ultrawideband polarization detection, their excessively high dark current restricts the development of ultraviolet-terahertz ultrawideband polarization detectors. Strain modulation is an important method for opening the bandgap in narrow bandgap semiconductors, providing a channel to reduce dark current. However, the fabrication of these detectors is typically performed on rigid Si / SiO2 substrates, making strain modulation impossible.
[0004] For example, the invention patent with publication number CN115832108A discloses a method for fabricating a gate-tunable high-sensitivity polarization detector, including a substrate, a first metal electrode, a PdSe2 / WSe2 two-dimensional van der Waals heterojunction, a graphene layer, and a second metal electrode; the substrate is a SiO2 / Si substrate; the PdSe2 / WSe2 two-dimensional van der Waals heterojunction includes a PdSe2 layer and a WSe2 layer; the bottom surface of the PdSe2 layer is disposed on the top surface of the substrate; the bottom surface of the WSe2 layer has a step, and the bottom surface of the WSe2 layer is disposed on both the top surface of the substrate and the top surface of the PdSe2 layer; the bottom surface of the graphene layer has a step, and the bottom surface of the graphene layer is disposed on both the top surface of the substrate and the top surface of the WSe2 layer; the bottom surface of the first metal electrode is disposed on the top surface of the PdSe2 layer, and the first metal electrode is not in contact with the WSe2 layer; the bottom surface of the second metal electrode is disposed on the top surface of the graphene layer. This invention is low in cost and simple in process. Through van der Waals heterojunction and gate modulation, it effectively suppresses dark current and greatly improves photosensitivity and response speed. However, because this invention is fabricated directly on a rigid SiO2 / Si substrate, it is difficult to control the strain in practical applications of this polarization detector.
[0005] In addition, existing polarization detector fabrication methods also suffer from the problem that the PDMS used in dry transfer comes into direct contact with the semiconductor material, which leads to severe surface organic molecule contamination and significant degradation of detector performance. Summary of the Invention
[0006] To address the technical problems of existing rigid substrate fabrication methods being unsuitable for strain control and the significant surface contamination caused by direct contact between PDMS and semiconductor materials, this invention proposes a strain-controlled room-temperature ultrawideband polarization detector fabrication method that features low surface contamination rate of photoelectric conversion materials, low fabrication cost, and strain-controlled dark current.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows: a method for fabricating a strain-controlled room-temperature ultrawideband polarization detector, comprising the following steps: S1: An aluminum oxide film is deposited on a polyimide film using atomic layer deposition technology to obtain film I; S2: The hexagonal boron nitride film and the PDMS film are bonded together to obtain film II; S3: Transfer the hexagonal boron nitride film on film II to the polyimide film on film I to obtain film III; S4: Preparation of ZrTe5 thin films; S5: By combining ZrTe5 thin film with thin film III, a strain-controlled photoelectric converter is obtained; S6: Using a thermal evaporation process, chromium and gold layers are deposited sequentially from top to bottom on the upper sides of both ends of a polyimide film to obtain a photoelectric converter with deposited metal interdigitated electrodes, i.e., a room temperature ultrawideband polarization detector.
[0008] The polyimide film thickness in step S1 is 25 μm, and the thickness of the deposited alumina film is 5-20 nm.
[0009] The method for bonding the hexagonal boron nitride film and the PDMS film together in step S2 is as follows: S21: Adhere bulk hexagonal boron nitride to Nitto-SPV224R tape, and tear the Nitto-SPV224R tape with hexagonal boron nitride attached multiple times to obtain hexagonal boron nitride nanosheets with a thickness of 4nm-20nm. S22: The hexagonal boron nitride side of the hexagonal boron nitride nanosheet is attached to the surface of the PDMS film to obtain film IV, and film IV is clamped and extruded for 24 hours using two rigid plates; S23: Remove the flexible plate and peel off the Nitto-SPV224R tape to obtain film II.
[0010] The method for transferring the hexagonal boron nitride film on film II to the polyimide film on film I in step S3 is as follows: S31: Place film I on the two-dimensional transfer platform with the polyimide film side facing up; S32: Slowly release film II so that the hexagonal boron nitride surface of film II comes into contact with the polyimide film surface of film I, so that the hexagonal boron nitride surface and the polyimide film surface are bonded together; S33: Using a two-dimensional transfer plane, heat film I and film II until the PDMS film can be slowly lifted and removed to obtain film III.
[0011] The method for preparing ZrTe5 thin films in step S4 is as follows: S41: Place a new PDMS film on a silicon wafer, use a pipette to drop-coat a PVA aqueous solution, and perform two spin coatings. S42: The silicon wafer is placed on a hot plate and heated to remove the liquid solvent on the surface. The PVA aqueous solution forms a smooth PVA film on the surface of the PDMS film, thus obtaining a PVA / PDMS film. S43: Adhere the bulk ZrTe5 onto Nitto-SPV224R tape, and repeatedly peel off the Nitto-SPV224R tape with ZrTe5 attached until a ZrTe5 film with a thickness of 300nm-700nm is obtained.
[0012] The concentration of the PVA aqueous solution is 5%.
[0013] The method of performing two spin coats in step S41 is as follows: first, spin coat at a speed of 1000-2000 rpm for 30-40 seconds, then increase the speed by 500 rpm / s, and then spin coat again at a speed of 1000-2000 rpm for 30-40 seconds.
[0014] The method for combining the ZrTe5 thin film with thin film III in step S5 is as follows: S51: Align the ZrTe5 film with film Ⅲ and place it so that the ZrTe5 surface of the ZrTe5 film is in contact with the hexagonal boron nitride surface of film Ⅲ and they are bonded together. S52: For the ZrTe5 film and film III that are bonded together, first heat them to 75-80℃ and maintain the temperature for 2-5 minutes, then cool them down to 40-50℃, and slowly lift and remove the PDMS film to obtain film V; S53: Immerse film V in deionized water at 60-70℃ for 15 minutes to remove PVA from film V and obtain strain-controlled photoelectric converter.
[0015] The metal interdigitated electrode in step S6 includes a gold layer and a chromium layer distributed sequentially from top to bottom. The chromium layer is disposed on top of the polyimide film. The ZrTe5 film and the hexagonal boron nitride film are both connected to the metal interdigitated electrode.
[0016] The strain-controlled room-temperature ultrawide polarization detector comprises a ZrTe5 thin film, a hexagonal boron nitride thin film, a polyimide thin film, and two interdigitated metal electrodes. The ZrTe5 thin film, hexagonal boron nitride thin film, and polyimide thin film are arranged sequentially from top to bottom. The two interdigitated metal electrodes are respectively located on the top two sides of the polyimide thin film. The two sides of the hexagonal boron nitride thin film and the polyimide thin film are respectively connected to the two interdigitated metal electrodes.
[0017] The beneficial effects of the present invention are: 1. The strain-controlled photoelectric converter of the present invention has a simple preparation process, and the preparation method has a low surface contamination rate of photoelectric conversion materials, low preparation cost, and dark current can be controlled by strain; 2. The strain-controlled photoelectric converter prepared by the present invention has a wide operating band, fast carrier transport speed, high temperature tolerance, and low dark current. It can not only realize intensity detection, but also polarization information detection, and has a wide range of detectable information dimensions. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1This is a schematic diagram of strain regulation of the strain-controlled photoelectric converter prepared in this invention.
[0020] Figure 2 This is a schematic diagram of the planar structure of the electrode layer of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared by the present invention.
[0021] Figure 3 This is a schematic diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared according to the present invention.
[0022] Figure 4 This is a diagram showing the electrical performance of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared according to Example 1 of the present invention.
[0023] Figure 5 This is the ultraviolet response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 1 of the present invention.
[0024] Figure 6 This is the terahertz response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 1 of the present invention.
[0025] Figure 7 This is the polarization selectivity response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 1 of the present invention.
[0026] Figure 8 This is a graph showing the electrical performance of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 2 of this invention.
[0027] Figure 9 This is the ultraviolet response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 2 of the present invention.
[0028] Figure 10 This is the terahertz response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 2 of the present invention.
[0029] Figure 11 This is the polarization selectivity response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 2 of the present invention.
[0030] Figure 12 This is a graph showing the electrical performance of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 3 of this invention.
[0031] Figure 13 This is the ultraviolet response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 3 of the present invention.
[0032] Figure 14 This is the terahertz response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 3 of the present invention.
[0033] Figure 15 This is the polarization selectivity response diagram of the ultraviolet-terahertz room temperature ultrawideband polarization detector prepared in Example 3 of the present invention. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Example 1 like Figure 1 As shown, a method for fabricating a strain-controlled room-temperature ultrawideband polarization detector includes the following steps: S1: An alumina film was deposited on a polyimide film using atomic layer deposition (ALD) to obtain film I. The polyimide film thickness was 25 μm, and the alumina film thickness was 10 nm. Alumina film thickness less than 5 nm would not be possible to form a film, while a thickness greater than 20 nm would reduce the flexibility of the alumina film and affect the performance of the room-temperature ultrawideband polarization detector.
[0036] S2: The hexagonal boron nitride film is bonded together with the PDMS (polydimethylsiloxane) film to obtain film II, specifically: S21: Adhere the bulk hexagonal boron nitride onto Nitto-SPV224R tape, and tear the Nitto-SPV224R tape with hexagonal boron nitride attached multiple times until a hexagonal boron nitride nanosheet with a thickness of 15nm is obtained. S22: The hexagonal boron nitride surface of the hexagonal boron nitride nanosheets is attached to the surface of a low-viscosity PDMS film to obtain film IV, and film IV is clamped and extruded for 24 hours using two soft plates; S23: Remove the flexible plate and peel off the Nitto-SPV224R tape to obtain film II.
[0037] S3: Transfer the hexagonal boron nitride film on film II to the polyimide film of film I to obtain film III. The specific method is as follows: S31: Place film I on the two-dimensional transfer platform with the polyimide film side facing up; S32: Slowly release film II so that the hexagonal boron nitride surface of film II comes into contact with the polyimide film surface of film I, so that the hexagonal boron nitride surface and the polyimide film surface are bonded together; S33: Using a heating module integrated on the two-dimensional transfer plane, films I and II are heated to 80°C and maintained for 15 minutes. The PDMS film is then slowly lifted and removed to obtain film III. During heating, the PDMS film becomes less viscous, making it easier to remove. Therefore, if the heating temperature is too low, the PDMS film will not lose its viscous properties, while if the temperature is too high, a large amount of residual adhesive will remain on the surface of film III. Furthermore, heating for less than 5 minutes will not cause the PDMS film to lose its viscous properties, while heating for more than 15 minutes will leave a large amount of residual adhesive on the surface of film III.
[0038] S4: Preparation of ZrTe5 thin films, the specific method is as follows: S41: Place a new PDMS film on a 7mm × 7mm silicon wafer, drop-coat a 5% PVA (polyvinyl alcohol) aqueous solution, and spin coat at 1000 rpm for 40 seconds, increasing the speed to 500 rpm / s, followed by spin coat at 2000 rpm for another 40 seconds. If the spin speed is below 1000 rpm, the PVA aqueous solution will not be able to form a film due to the low speed, while a spin speed above 2000 rpm will result in poor film quality. If the spin coat time is too short, the film thickness will be uneven; if the spin coat time is too long, the film thickness will be too small to complete subsequent processes. In addition, a single spin coat cannot form a sufficiently flat and uniform film, so a second spin coat is required to prepare a high-quality film. The preparation of the PVA film effectively reduces the surface contamination rate of the photoelectric conversion material.
[0039] S42: Place the silicon wafer on a hot plate and heat it at 70°C for 1 minute to remove the liquid solvent on the surface and obtain a PVA / PDMS film.
[0040] S43: Adhere the bulk ZrTe5 onto Nitto-SPV224R tape, and repeatedly peel off the Nitto-SPV224R tape with ZrTe5 attached to it to obtain a ZrTe5 film with a thickness of 552nm.
[0041] S5: By combining the ZrTe5 thin film with thin film III, a strain-modulated photoelectric converter is obtained. The specific method is as follows: S51: Align the ZrTe5 film with film Ⅲ and place it so that the ZrTe5 surface of the ZrTe5 film is in contact with the hexagonal boron nitride surface of film Ⅲ and they are bonded together. S52: The ZrTe5 film and film III, which are bonded together, are heated to 75°C for 2 minutes and then cooled to 45°C. The PDMS film is then slowly lifted and removed to obtain film V. Specifically, the PDMS film can be de-adhesive at 75-80°C, but excessively high temperatures will cause deformation of the PVA film in film III, which in turn will lead to deformation of the ZrTe5 film, severely weakening the performance of the room-temperature ultra-wideband polarization detector. Therefore, the heating temperature needs to be controlled between 75-80°C, and the heating time should be controlled between 2-5 minutes. Simultaneously, since lowering the temperature will increase the adhesion of the PDMS film, preventing the ZrTe5 film from being released onto the hexagonal boron nitride, considering all factors, releasing the ZrTe5 film at a temperature between 40-50°C is the optimal solution to ensure the ZrTe5 film is released onto the hexagonal boron nitride.
[0042] S53: Immerse film V in deionized water at 60°C for 15 minutes to remove the PVA film on film V, obtaining a strain-controlled photoelectric converter. Since the films constituting the strain-controlled photoelectric converter all possess a certain degree of bending deformation capability, the strain-controlled photoelectric converter can achieve strain regulation. S6: As Figure 2 As shown, the interdigitated metal electrodes are fabricated using a thermal evaporation process. Chromium and gold layers are deposited separately to form chromium and gold layers as electrodes, with the chromium layer positioned beneath the gold layer. The chromium layer has a thickness of 5 nm, and the gold layer has a thickness of 40 nm. The bottom of the chromium layer is positioned on top of the polyimide film. The sides of the interdigitated metal electrodes are connected to the ZrTe5 film and hexagonal boron nitride. A strain-controlled photoelectric converter with the electrodes mounted is placed on a movable fixture. By controlling the displacement of the movable fixture using a stepper motor, the strain is controlled, causing a change in the ZrTe5 lattice constant. This change in the ZrTe5 lattice constant leads to the opening of the bandgap, ultimately achieving dark current control.
[0043] The strain-modulated room-temperature ultrawide polarization detector includes a ZrTe5 thin film, a hexagonal boron nitride thin film, a polyimide thin film, and two metal interdigitated electrodes. The ZrTe5 thin film, hexagonal boron nitride thin film, and polyimide thin film are arranged sequentially from top to bottom. The two metal interdigitated electrodes are respectively disposed on the top two sides of the polyimide thin film. The two sides of the hexagonal boron nitride thin film and the polyimide thin film are respectively connected to the two metal interdigitated electrodes.
[0044] The electrical conductivity of the fabricated strain-controlled photoelectric converter was tested. After connecting both ends of the material to conductive probes using a microprobe stage, current-voltage measurements were performed using a source meter. The test results are as follows: Figure 4 The strain-controlled photoelectric converter exhibits good conductivity and displays ohmic contact characteristics.
[0045] The prepared ultraviolet-terahertz room-temperature ultrawide polarization detector was subjected to photoelectric information detection under 355nm laser and 220GHz terahertz source conditions, respectively. The photocurrent test results are as follows: Figure 5 and Figure 6 As shown, the ultraviolet-terahertz room-temperature ultrawideband polarization detector can achieve photoelectric response across the entire 355nm ultraviolet band to 220GHz terahertz band. Furthermore, due to strain modulation, the detector's dark current is as low as the picoampere level. In addition, the polarization detection capability of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was tested using a polarized light source. The photocurrent of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was read at different polarization angles, and the test results are as follows. Figure 7 The ultraviolet-terahertz room temperature ultrawideband polarization detector can achieve a polarization ratio of 3.4, possessing excellent polarization detection capabilities.
[0046] Example 2 A method for fabricating a strain-controlled room-temperature ultrawideband polarization detector includes the following steps: S1: An alumina film is deposited on a polyimide film using atomic layer deposition (ALD) technology to obtain film I. The polyimide film has a thickness of 25 μm, and the deposited alumina film has a thickness of 5 nm.
[0047] S2: The hexagonal boron nitride film is bonded together with the PDMS (polydimethylsiloxane) film to obtain film II, specifically: S21: Adhere bulk hexagonal boron nitride to Nitto-SPV224R tape, and tear the Nitto-SPV224R tape with hexagonal boron nitride attached multiple times to obtain hexagonal boron nitride nanosheets with a thickness of 4nm. S22: The hexagonal boron nitride side of the hexagonal boron nitride nanosheet is attached to the surface of the PDMS film to obtain film IV, and film IV is clamped and extruded for 24 hours using two rigid plates; S23: Remove the rigid board and peel off the Nitto-SPV224R tape to obtain film II.
[0048] S3: Transfer the hexagonal boron nitride film on film II to the polyimide film of film I to obtain film III. The specific method is as follows: S31: Place film I on the two-dimensional transfer platform with the polyimide film side facing up; S32: Slowly release film II so that the hexagonal boron nitride surface of film II comes into contact with the polyimide film surface of film I, so that the hexagonal boron nitride surface and the polyimide film surface are bonded together; S33: Using a two-dimensional transfer plane, heat film I and film II to 80°C and maintain for 15 minutes. Slowly lift and remove the PDMS film to obtain film III.
[0049] S4: Preparation of ZrTe5 thin films, the specific method is as follows: S41: Place a new PDMS film on a 7mm×7mm silicon wafer, drop a 5% PVA (polyvinyl alcohol) aqueous solution onto it, and spin coat it at 1500 rpm for 35 seconds, then increase the speed to 500 rpm / s, and then spin coat it again at 1500 rpm for 35 seconds.
[0050] S42: Place the silicon wafer on a hot plate and heat it at 70°C for 1 minute to remove the liquid solvent on the surface and obtain a PVA / PDMS film.
[0051] S43: Adhere the bulk ZrTe5 onto Nitto-SPV224R tape, and repeatedly peel off the Nitto-SPV224R tape with ZrTe5 attached to it to obtain a ZrTe5 film with a thickness of 300nm.
[0052] S5: By combining the ZrTe5 thin film with thin film III, a strain-modulated photoelectric converter is obtained. The specific method is as follows: S51: Align the ZrTe5 film with film Ⅲ and place it so that the ZrTe5 surface of the ZrTe5 film is in contact with the hexagonal boron nitride surface of film Ⅲ and they are bonded together. S52: The ZrTe5 film and film III, which are bonded together, are heated to 77°C for 3 minutes and cooled to 40°C. The PDMS film is then slowly lifted and removed to obtain film V. S53: Immerse film V in deionized water at 65°C for 15 minutes to remove PVA from film V and obtain strain-controlled photoelectric converter.
[0053] S6: The metal interdigital electrode mask is fixed to both ends of the strain-controlled photoelectric converter using high-temperature tape. The bottom of the metal interdigital electrode is placed on the polyimide film. The metal interdigital electrode is deposited by thermal evaporation, with chromium and gold as electrodes respectively, where the chromium thickness is 5nm and the gold thickness is 40nm.
[0054] The electrical conductivity of the fabricated strain-controlled photoelectric converter was tested. After connecting both ends of the material to conductive probes using a microprobe stage, current-voltage measurements were performed using a source meter. The test results are as follows: Figure 8 The strain-controlled photoelectric converter exhibits good conductivity and displays ohmic contact characteristics.
[0055] The prepared ultraviolet-terahertz room-temperature ultrawide polarization detector was subjected to photoelectric information detection under 355nm laser and 220GHz terahertz source conditions, respectively. The photocurrent test results are as follows: Figure 9 and Figure 10As shown, the ultraviolet-terahertz room-temperature ultrawideband polarization detector can achieve photoelectric response across the entire 355nm ultraviolet band to 220GHz terahertz band. Furthermore, due to strain modulation, the detector's dark current is as low as the picoampere level. In addition, the polarization detection capability of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was tested using a polarized light source. The photocurrent of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was read at different polarization angles, and the test results are as follows. Figure 11 The ultraviolet-terahertz room temperature ultrawideband polarization detector can achieve a polarization ratio of 3.4, possessing excellent polarization detection capabilities.
[0056] The other structures and principles are the same as in Example 1.
[0057] Example 3 A method for fabricating a strain-controlled room-temperature ultrawideband polarization detector includes the following steps: S1: An alumina film is deposited on a polyimide film using atomic layer deposition (ALD) technology to obtain film I. The polyimide film has a thickness of 25 μm, and the deposited alumina film has a thickness of 20 nm.
[0058] S2: The hexagonal boron nitride film is bonded together with the PDMS (polydimethylsiloxane) film to obtain film II, specifically: S21: Adhere bulk hexagonal boron nitride to Nitto-SPV224R tape, and tear the Nitto-SPV224R tape with hexagonal boron nitride attached multiple times to obtain hexagonal boron nitride nanosheets with a thickness of 20nm. S22: The hexagonal boron nitride side of the hexagonal boron nitride nanosheet is attached to the surface of the PDMS film to obtain film IV, and film IV is clamped and extruded for 24 hours using two rigid plates; S23: Remove the rigid board and peel off the Nitto-SPV224R tape to obtain film II.
[0059] S3: Transfer the hexagonal boron nitride film on film II to the polyimide film of film I to obtain film III. The specific method is as follows: S31: Place film I on the two-dimensional transfer platform with the polyimide film side facing up; S32: Slowly release film II so that the hexagonal boron nitride surface of film II comes into contact with the polyimide film surface of film I, so that the hexagonal boron nitride surface and the polyimide film surface are bonded together; S33: Using a two-dimensional transfer plane, heat film I and film II to 80°C and maintain for 15 minutes. Slowly lift and remove the PDMS film to obtain film III.
[0060] S4: Preparation of ZrTe5 thin films, the specific method is as follows: S41: Place a new PDMS film on a 7mm×7mm silicon wafer, drop a 5% PVA (polyvinyl alcohol) aqueous solution onto it, and spin coat it at 2000 rpm for 30 seconds, then increase the speed to 500 rpm / s, and then spin coat it again at 2000 rpm for 30 seconds.
[0061] S42: Place the silicon wafer on a hot plate and heat it at 70°C for 1 minute to remove the liquid solvent on the surface and obtain a PVA / PDMS film.
[0062] S43: Adhere the bulk ZrTe5 onto Nitto-SPV224R tape, and repeatedly peel off the Nitto-SPV224R tape with ZrTe5 attached to it to obtain a ZrTe5 film with a thickness of 700nm.
[0063] S5: By combining the ZrTe5 thin film with thin film III, a strain-modulated photoelectric converter is obtained. The specific method is as follows: S51: Align the ZrTe5 film with film Ⅲ and place it so that the ZrTe5 surface of the ZrTe5 film is in contact with the hexagonal boron nitride surface of film Ⅲ and they are bonded together. S52: The ZrTe5 film and film III, which are bonded together, are heated to 80°C for 5 minutes and cooled to 50°C. The PDMS film is then slowly lifted and removed to obtain film V. S53: Immerse film V in deionized water at 70°C for 15 minutes to remove PVA from film V and obtain strain-controlled photoelectric converter.
[0064] S6: The metal interdigital electrode mask is fixed to both ends of the strain-controlled photoelectric converter using high-temperature tape. The bottom of the metal interdigital electrode is placed on the polyimide film. The metal interdigital electrode is deposited by thermal evaporation, with chromium and gold as electrodes respectively, where the chromium thickness is 5nm and the gold thickness is 40nm.
[0065] The electrical conductivity of the fabricated strain-controlled photoelectric converter was tested. After connecting both ends of the material to conductive probes using a microprobe stage, current-voltage measurements were performed using a source meter. The test results are as follows: Figure 12 The strain-controlled photoelectric converter exhibits good conductivity and displays ohmic contact characteristics.
[0066] The prepared ultraviolet-terahertz room-temperature ultrawide polarization detector was subjected to photoelectric information detection under 355nm laser and 220GHz terahertz source conditions, respectively. The photocurrent test results are as follows: Figure 13 and Figure 14As shown, the ultraviolet-terahertz room-temperature ultrawideband polarization detector can achieve photoelectric response across the entire 355nm ultraviolet band to 220GHz terahertz band. Furthermore, due to strain modulation, the detector's dark current is as low as the picoampere level. In addition, the polarization detection capability of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was tested using a polarized light source. The photocurrent of the ultraviolet-terahertz room-temperature ultrawideband polarization detector was read at different polarization angles, and the test results are as follows. Figure 15 The ultraviolet-terahertz room temperature ultrawideband polarization detector can achieve a polarization ratio of 3.4, possessing excellent polarization detection capabilities.
[0067] The other structures and principles are the same as in Example 2.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for fabricating a strain-controlled room-temperature ultrawideband polarization detector, characterized in that, Includes the following steps: S1: An aluminum oxide film is deposited on a polyimide film using atomic layer deposition technology to obtain film I; S2: The hexagonal boron nitride film and the PDMS film are bonded together to obtain film II; S3: Transfer the hexagonal boron nitride film on film II to the polyimide film on film I to obtain film III; S4: Preparation of ZrTe5 thin films; S5: By combining ZrTe5 thin film with thin film III, a strain-controlled photoelectric converter is obtained; S6: Using a thermal evaporation process, chromium and gold layers are deposited sequentially from top to bottom on the upper sides of both ends of a polyimide film to obtain a photoelectric converter with deposited metal interdigitated electrodes, i.e., a room temperature ultrawide polarization detector. The method for preparing ZrTe5 thin films in step S4 is as follows: S41: Place a new PDMS film on a silicon wafer, use a pipette to drop-coat a PVA aqueous solution, and perform two spin coatings. S42: The silicon wafer is placed on a hot plate and heated to remove the liquid solvent on the surface. The PVA aqueous solution forms a smooth PVA film on the surface of the PDMS film, thus obtaining a PVA / PDMS film. S43: Adhere the bulk ZrTe5 onto Nitto-SPV224R tape, and repeatedly peel off the Nitto-SPV224R tape with ZrTe5 attached until a ZrTe5 film with a thickness of 300nm-700nm is obtained.
2. The method for fabricating a strain-controlled room-temperature ultrawideband polarization detector according to claim 1, characterized in that, The polyimide film thickness in step S1 is 25 μm, and the thickness of the deposited alumina film is 5-20 nm.
3. The method for fabricating a strain-controlled room-temperature ultrawideband polarization detector according to claim 2, characterized in that, The method for bonding the hexagonal boron nitride film and the PDMS film together in step S2 is as follows: S21: Adhere bulk hexagonal boron nitride to Nitto-SPV224R tape, and tear the Nitto-SPV224R tape with hexagonal boron nitride attached multiple times to obtain hexagonal boron nitride nanosheets with a thickness of 4nm-20nm. S22: The hexagonal boron nitride side of the hexagonal boron nitride nanosheet is attached to the surface of the PDMS film to obtain film IV, and film IV is clamped and extruded for 24 hours using two rigid plates; S23: Remove the flexible plate and peel off the Nitto-SPV224R tape to obtain film II.
4. The method for fabricating a strain-controlled room-temperature ultrawideband polarization detector according to claim 3, characterized in that, The method for transferring the hexagonal boron nitride film on film II to the polyimide film on film I in step S3 is as follows: S31: Place film I on the two-dimensional transfer platform with the polyimide film side facing up; S32: Slowly release film II so that the hexagonal boron nitride surface of film II comes into contact with the polyimide film surface of film I, so that the hexagonal boron nitride surface and the polyimide film surface are bonded together; S33: Using a two-dimensional transfer plane, heat film I and film II until the PDMS film can be slowly lifted and removed to obtain film III.
5. The method for fabricating a strain-modulated room-temperature ultrawideband polarization detector according to any one of claims 1-4, characterized in that, The concentration of the PVA aqueous solution is 5%.
6. The method for fabricating a strain-controlled room-temperature ultrawideband polarization detector according to claim 5, characterized in that, The method of performing two spin coats in step S41 is as follows: first, spin coat at a speed of 1000-2000 rpm for 30-40 seconds, then increase the speed by 500 rpm / s, and then spin coat again at a speed of 1000-2000 rpm for 30-40 seconds.
7. The method for fabricating a strain-controlled room-temperature ultrawideband polarization detector according to claim 6, characterized in that, The method for combining the ZrTe5 thin film with thin film III in step S5 is as follows: S51: Align the ZrTe5 film with film Ⅲ and place it so that the ZrTe5 surface of the ZrTe5 film is in contact with the hexagonal boron nitride surface of film Ⅲ and they are bonded together. S52: For the ZrTe5 film and film III that are bonded together, first heat them to 75-80℃ and maintain the temperature for 2-5 minutes, then cool them down to 40-50℃, and slowly lift and remove the PDMS film to obtain film V; S53: Immerse film V in deionized water at 60-70℃ for 15 minutes to remove PVA from film V and obtain strain-controlled photoelectric converter.
8. The method for fabricating a strain-modulated room-temperature ultrawideband polarization detector according to claim 6 or 7, characterized in that, The metal interdigitated electrode in step S6 includes a gold layer and a chromium layer distributed sequentially from top to bottom. The chromium layer is disposed on top of the polyimide film. The ZrTe5 film and the hexagonal boron nitride film are both connected to the metal interdigitated electrode.
9. A strain-controlled room-temperature ultrawideband polarization detector fabricated using the method described in any one of claims 1-8, characterized in that, It includes a ZrTe5 film, a hexagonal boron nitride film, a polyimide film, and two metal interdigitated electrodes. The ZrTe5 film, hexagonal boron nitride film, and polyimide film are arranged sequentially from top to bottom. The two metal interdigitated electrodes are respectively arranged on the top two sides of the polyimide film. The two sides of the hexagonal boron nitride film and the polyimide film are respectively connected to the two metal interdigitated electrodes.
Citation Information
Patent Citations
Preparation method of grid-adjustable high-sensitivity polarization detector
CN115832108A
Strain-regulated flexible wearable photoelectric detector and preparation method thereof
CN114899255A
KR20200050380A
